Local Politics Post-Reform Era: The Roles of Muhammadiyah in the 2004-2014 DPD’s Election in Yogyakarta Special Regions, Indonesia - Amriyanto, Husni; Efendi, David (Universitas Muhammadiyah Yogyakarta, 2018)
After post-Reform Indonesia, Indonesia has been employing a dramatic decentralization practice in Indonesia nationwide. Since 1999, Indonesia has been electing for representative council (DPR RI) and regional representation so called DPD RI in very direct way. This paper aims to analyse the local politics especially at the case of DPD’s election in Yogyakarta special region of Indonesia in the competition process among the different group interests which are Islamic group (Muhammadiyah, NU, PKS), Kraton /aristocrat interest, and nationalist group interest (PDI-P). Those groups are the big four that have been playing important role in the competition in DPD election sequentially in 2004, 2009, and 2014. In Yogyakarta special region, four members of DPD since the first election has been represented by three Islamic group both modern and traditional ones and by Yogyakarta palace. this paper more focus on the 2014 election which were followed by more competitor from Pakualaman palace, and also from nationalist group that have same mass with the Palace. this competition was really interesting to explain, how people decide their representative members and how different group compete each other in this election. Also, what strategy and by manner they collect voters in this individual based-individual candidate election. From the field research, it can be concluded at least there are three point (1) each candidate was strongly endorsed by established organization and community to support for the election since 2004. So, four incumbents easy to win the competition; (2) the success team have many thing in common for example the focus on the core of supporter (basis masa) by using strategy ‘by name by address list”; and lastly (3) they were employing any symbolic that really easy to understand for the common people such as Islamic value, organization value, ideology, etc. by adopting many social activity and ritual in promoting candidates for example club goods, voluntary organization, and other forms of informal communities.